Balance Technologies for Calculating and Predictive Estimation of Labor Resources for Regional Socio-Economic Systems - V. A. Kurzenev; V. T. Perekrest; I. V. Perekrest (Управленческое консультирование)
The article analyzes the institutional and technological features of the calculus (representation) and predictive assessment of the balance of labor resources for regional economic systems.The review is carried out in the general context of the particular tasks of developing egional strategies: goal-setting, analysis and forecasting.The theoretical and practical experience of the laboratory of mathematical methods of data analysis of IPRE RAS and St. Petersburg EMI RAS (until 2018) in the framework of the direction “Economic and mathematical methods for state regulation of socially oriented economies at the regional level within the framework of innovative development models” is presented.